AKKELIES VAN NES, CLAUDIA YAMU - Introduction to Space Syntax in Urban Studies - Ezquerra, Isabel (ZARCH, 2023)
Akkelies van Nes, Claudia YamuIntroduction to Space Syntax in Urban StudiesCham (Switzerland): Springer, 2021. 250 pp. Tapa dura. Idioma: inglés. 51,99 €ISBN: 978-3-030-59139-7DOI: 10.1007/978-3-030-59140-3